Pemberdayaan Mahasiswa Melalui Program Kampus Mengajar: Kolaborasi dengan Sekolah untuk Peningkatan Literasi dan Numerasi di Pematangsiantar - Hengki Mangiring Parulian Simarmata; Erikson Damanik; Erwin Sirait; Doris Yolanda Saragih (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
The teaching campus program is one of the independent campus programs, an initiative from the Ministry of Education to improve the quality of education in schools throughout Indonesia. This article reviews the service carried out by Field Supervisor Lecturers with students from Nommensen University Pematangsiantar and Simalungun University who carried out service at Taman Siswa Private Middle School and Kartika Pematangsiantar Private Middle School in 2024. The main focus of this service is strengthening literacy and numeracy through creative and innovative approaches. This article discusses mentoring activities, evaluations, and challenges faced during the program. Based on monitoring results, this program increased student motivation in literacy and numeracy and fostered collaborative skills among students..